# Algebra

Content type
User Generated
Subject
Algebra
Type
Homework
Rating
Showing Page:
1/1
Solution
Let u = x
2
+ 1 and rewrite the given equation in terms of u as follows
u
2
+ 2u - 3 = 0
Factor and solve the above equation
(u + 3)(u - 1) = 0
two solutions: u = x
2
+ 1 = - 3 and u = x
2
+ 1 = 1
Equation x
2
+ 1 = - 3 has no solutions. Solve the equation x
2
+ 1 = 1 for to get
x = 0.
The given equation has one solution.

Unformatted Attachment Preview
Solution Let u = x2 + 1 and rewrite the given equation in terms of u as follows u 2 + 2u - 3 = 0 Factor and solve the above equation (u + 3)(u - 1) = 0 two solutions: u = x2 + 1 = - 3 and u = x2 + 1 = 1 Equation x2 + 1 = - 3 has no solutions. Solve the equation x2 + 1 = 1 for to get x = 0. The gi ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

### Review

Anonymous
I was stuck on this subject and a friend recommended Studypool. I'm so glad I checked it out!

Studypool
4.7
Indeed
4.5
Sitejabber
4.4